Puppen - Körper - Automaten : Phantasmen der Moderne - Kunstsammlung Nordrhein-Westfalen, Düsseldorf; Bredekamp, Horst; Dotzler, Bernhard J.; Filipovic, Elena; Gassner, Hubertus; Hille, Karoline; Krystof, Doris; Kuni, Verena; Käufer, Birgit; Lüdeking, Karlheinz; Müller, Maria; Müller-Tamm, Pia; et al. (Düsseldorf : Kunstsammlung Nordrhein-Westfalen Düsseldorf, 1999)
Albers, Josef ; Aluf, Nic ; Archipenko, Aleksandr ; Atget, Eugène ; Baquié, Richard ; Baumeister, Willi ; Bayer, Herbert ; Beckmann, Max ; Belling, Rudolf ; Bellmer, Denise ; Bellmer, Hans ; Berco, Ferenc ; Biermann, Aenne ; Blumenfeld, Erwin ; Bortnyik, Sándor ; Boucher, Pierre ; Brassai, Georges ; Brauner, Victor ; Breton, André ; Cahun, Claude ; Carrà, Carlo ; Citroen, Paul ; Coppola, Horacio ; Cornell, Joseph ; Crotti, Jean ; Dali, Salvador ; De Chirico, Giorgio ; Depero, Fortunato ; Dix, Otto ; Dominguez, Oscar ; Duchamp, Marcel ; Ernst, Max ; Exter, Alexandra ; Francés, Esteban ; Freddie, Wilhelm ; Freund, Gisèle ; Funke, Jaromir ; Gontscharowa, Natalia ; Grosz, George ; Hausmann, Raoul ; Heartfield, John ; Hoerle, Heinrich ; Huszar, Vilmos ; Höch, Hannah ; Jahan, Pierre ; Jawlensky, Alexej von ; Keetman, Peter ; Kertesz, André ; Kokoschka, Oskar ; Krull, Germaine ; Lamba, Jacqueline ; Leger, Fernand ; Lissitzky, El ; List, Herbert ; Maar, Dora ; Magritte, René ; Malevich, Kasimir ; Man Ray ; Masson, Andre ; Michel, Robert ; Miro, Joan ; Moholy-Nagy, Laszlo ; Molinier, Pierre ; Morach, Otto ; Morandi, Giorgio ; Münter, Gabriele ; Paris, Gaston ; Picabia, Francis ; Podsadecki, Kazimierz ; Ringl + pit ; Rohde, Werner ; Saad, Georges ; Schenker, Karl ; Schlemmer, Oskar ; Schlichter, Rudolf ; Schreyer, Lothar ; Seiwert, Franz Wilhelm ; Sert, José Maria ; Stepanowa, Warwara ; Stoecklin, Niklaus ; Styrsky, Jindrich ; Sudek, Josef ; Taeuber-Arp, Sophie ; Tanguy, Yves ; Teige, Karel ; Ubac, Raoul ; Umbo ; Valadon, Suzanne ; Villon, Jacques ; Wacker, Rudolf ; Wols ; Yamawaki, Iwao
Puppen - Körper - Automaten : Phantasmen der Moderne, Kunstsammlung Nordrhein-Westfalen Düsseldorf, 24. Juli bis 17. Oktober 1999
Duits
boek